Immuno-protective effect of commercial IBD vaccines against emerging novel variant infectious bursal disease virus in specific-pathogen-free chickens - Aliyu, Hayatuddeen Bako; Hamisu, Tasiu Mallam; Hair-Bejo, Mohd; Omar, Abdul Rahman; Ideris, Aini (Korean Society of Veterinary Science, 2024)
Importance: Infectious bursal disease (IBD) is an important viral poultry disease that vaccination can control. Objective: This study examined the immune protection of immune-complex (Vaccine A) and attenuated live (Vaccine B) IBD vaccines in specific-pathogen-free (SPF) chickens against a novel Malaysian variant IBD virus (vaIBDV) challenge. Methods: One-day-old (n =75) SPF chickens were divided randomly into the following three groups of 25 chicks each: Control, Vaccine A, and Vaccine B groups. The vaIBDV strain, UPM1432/2019, was used for the challenge at 21 and 28days post-vaccination (dpv). Five birds from unchallenged and challenged groups were sacrificed seven days post-challenge, and blood, bursa, spleen, and cloacal swabs were collected. The IBD antibodies (Abs), lymphoid lesions, and viral load were determined. Results: The UPM1432/2019 virus induced bursal damage in vaccinated SPF chickens despite Ab titers. The mean Ab titers of the Vaccine A challenged group were significantly lower (p < 0.002) than in the unchallenged group at 28 dpv. The bursal indices of the vaccinated unchallenged groups did not differ significantly from those of the vaccinated challenged groups (p = 0.94). Microscopically, the bursae of the challenged groups showed significant atrophy. The bursal lesion score was higher (p < 0.05) in the control and Vaccine B challenged groups than the Vaccine A challenged group. The challenged group had a higher viral load than the vaccinated groups (p < 0.001). Conclusions and Relevance: Neither vaccine fully protected against a vaIBDV challenge, highlighting the limitations of current vaccines and the need for further research.